Breaking the Iron Homeostasis: A ?Trojan Horse? Self-Assembled Nanodrug Sensitizes Homologous Recombination Proficient Ovarian Cancer Cells to PARP Inhibition br - Li Yangyang; Cen Yixuan; Fang Yifeng; Tang Sangsang; Li Sen; Ren Yan; Zhang Hongbo; Lu Weiguo; Xu Junfen (AMER CHEMICAL SOC, 2025)
Poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors are used in ovarian cancer treatment and have greatly improved the survival rates for homologous recombination repair (HRR)-deficient patients. However, their therapeutic efficacy is limited in HRR-proficient ovarian cancer. Thus, sensitizing HRRproficient ovarian cancer cells to PARP inhibitors is important in clinical practice. Here, a nanodrug, olaparib-Ga, was designed using self-assembly of the PARP inhibitor olaparib into bovine serum albumin through gallic acid gallium(III) coordination nu ia a convenient and green synthetic method. Compared with olaparib, olaparib-Ga featured an ultrasmall size of 7 nm and led to increased suppression of cell viability, induction of DNA damage, and enhanced cell apoptosis in the SKOV3 and OVCAR3 HRR-proficient ovarian cancer cells in nu itro. Further experiments indicated that the olaparib-Ga nanodrug could suppress RRM2 expression, activate the Fe2+/ROS/ MAPK pathway and HMOX1 signaling, inhibit the PI3K/AKT signaling pathway, and enhance the expression of cleaved-caspase 3 and BAX protein. This, in turn, led to increased cell apoptosis in HRR-proficient ovarian cancer cells. Moreover, olaparib-Ga effectively restrained SKOV3 and OVCAR3 tumor growth and exhibited negligible toxicity in nu i nu o. In conclusion, we propose that olaparib-Ga can act as a promising nanodrug for the treatment of HRR-proficient ovarian cancer.